2017
DOI: 10.1590/1980-5373-mr-2016-0466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing Parameters on Microstructure and Mechanical Properties of Powder-Thixoforged SiC p /6061 Al Composite

Abstract: A novel processing technology for the fabrication of particle reinforced metal matrix composites, powder thixoforming (PTF), was proposed and 6061 Al-based composites reinforced with 10% volume fractions of SiC particles (SiC p ) were fabricated. The effects of processing parameters, such as reheating time, mould temperature and reheating temperature, on its microstructure and mechanical properties were investigated. The results indicated that all the three processing parameters exerted a significant influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…BARMOUZ et al [27] has discovered the formation of the intermetallic phases between the base metal and reinforced particles in the casted specimens. CAO et al [28] has discovered that the behavior of the reinforced particles changes with the processing parameters. GUKENDRAN et al [29] concluded that the introduction of reinforcements into aluminium enhances the mechanical properties of the composites considerably.…”
Section: Introductionmentioning
confidence: 99%
“…BARMOUZ et al [27] has discovered the formation of the intermetallic phases between the base metal and reinforced particles in the casted specimens. CAO et al [28] has discovered that the behavior of the reinforced particles changes with the processing parameters. GUKENDRAN et al [29] concluded that the introduction of reinforcements into aluminium enhances the mechanical properties of the composites considerably.…”
Section: Introductionmentioning
confidence: 99%